Using of steganographic methods in questions of state information resources protection - Юдін, О.К.; Симониченко, Я.А.; Симониченко, А.А. (Science-based technologies, 2017)
The article deals with the definition of the possibilities of using steganographic methods, namely, methods of information hiding and steganography analysis, in problems of protection of state information resources. During the work was identified the opportunity of the application of steganographic techniques to meet the requirements of protection’s services of information in information telecommunication systems where information is processed, with the aim of the implementation of protection’s systems in the integrated systems of information protection or protection mechanisms in the software or technical means of information protection. It was the research of the implementation of the steganographic methods of information hiding and steganographic analysis, their characteristics and applications. Based on the conducted research identified services of the information security, implementation of which can be used steganography techniques information hiding and steganographic analysis.